The Role of Emotion Regulation in the Relationship Between Trauma and Health-Related Outcomes. Issue 3 (3rd April 2019) - Hofman, Nicole L.; Simons, Raluca M.; Simons, Jeffrey S.; Hahn, Austin M.
Abstract: The current study examined emotion regulation variables (alexithymia, negative urgency, distress tolerance) and their relationship to traumatic event exposure, emotional intelligence (EI), and health outcomes: posttraumatic stress (PTS) symptoms, antisocial behaviors, alcohol use, and alcohol-related problems. Data from 561 undergraduate students and structural equation modeling was used to test the hypotheses. Results indicated both traumatic experiences and EI predicted PTS symptoms directly and indirectly, via alexithymia and distress tolerance. Conversely, traumatic experiences and EI predicted antisocial behaviors and both alcohol outcomes directly and indirectly. EI was indirectly related to alcohol-related problems via PTS and antisocial behaviors, regardless of alcohol consumption.